Kajian Pertumbuhan Dan Biomassa Perakaran Stek Pucuk Stevia Akibat Pupuk Kandang Di Tanah Gambut Kota Palangka Raya - Djoko Eko Hadi Susilo (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
The cultivation of Stevia in peat soil has ever done. In the present, to cultivate Stevia in peat soils is necessary to get the substitution of sugar needs and as an alternative natural sweetener for food and beverage. The aim of this study is to know how far the influence of the using of stable fertilizer to the capability of the growth and biomass of the root on the cutting of the Stevia shoots in the peat soil city of Palangka Raya. The stable fertilizer that was used in this study is chicken feces. The results of this study are expected as a material of the study to support the development of cultivation of Stevia in the peat soil. This study was conducted using a polybag on Wortel street, Panarung of the District of Pahandut of the Palangkaraya city from February to April 2016. The data of the observation were collected to the growth of the longest root length (cm) and root biomass (g) of Stevia plants at the age of 10, 20, 30, and 40 HST. The results of the study showed that the using of chicken feces as the stable fertilizer to the Stevia plant has affected to the growth of the longest root length and root biomass of Stevia plant at the age of 10, 20, 30 and 40 days after planting. The result of this study also requires a further detailed study on the growth of the number, diameter, and surface of the roots area.